Hubungan Hasil Belajar Akidah Akhlak dengan Kedisiplinan Peserta Didik di Madrasah Diniyah Miftahul Huda - Putri Maya Sari; Retno Widyaningrum; Zennanta Agustia (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Madrasah diniyah has a distinct role in strengthening religious knowledge and everyday discipline among Muslim learners. This study examines the relationship between Akidah Akhlak learning outcomes and students’ discipline at Madrasah Diniyah Miftahul Huda. A quantitative correlational design was applied to 31 students using total sampling. Akidah Akhlak learning outcomes were calculated from Tauhid and Akhlaq scores, while students’ discipline was proxied by an attendance-based discipline score because the attitude column in the ledger was homogeneous. Data were analyzed through descriptive statistics, Shapiro-Wilk normality tests, Pearson correlation, and simple linear regression. The results show that the mean Akidah Akhlak learning outcome was 76.76 with a standard deviation of 7.92, while the mean discipline score was 94.61 with a standard deviation of 4.08. Both variables were normally distributed. Pearson correlation produced r = -0.083 with Sig. = 0.658, indicating no significant relationship. Regression analysis yielded R Square = 0.007, meaning that learning outcomes explained only 0.7% of the variance in discipline. These findings suggest that discipline in madrasah diniyah is shaped more by habituation, institutional culture, supervision, and family environment than by cognitive achievement alone.